Clonal haematopoiesis of indeterminate potential and impaired kidney function—A Danish general population study with 11 years follow‐up. (21st August 2022) - Larsen, Morten K.; Skov, Vibe; Kjær, Lasse; Møller‐Palacino, Natascha A.; Pedersen, Rasmus K.; Andersen, Morten; Ottesen, Johnny T.; Cordua, Sabrina; Poulsen, Henrik E.; Dahl, Morten; Knudsen, Trine A.; Eickhardt‐Dalbøge, Christina Schjellerup; et al.
Abstract: The myeloproliferative neoplasms are associated with chronic kidney disease but whether clonal haematopoiesis of indeterminate potential (CHIP) is associated with impaired kidney function is unknown. In the Danish General Suburban Population Study ( N = 19 958) from 2010 to 2013, 645 individuals were positive for JAK2V617F ( N = 613) or CALR ( N = 32) mutations. Mutation‐positive individuals without haematological malignancy were defined as having CHIP ( N = 629). We used multiple and inverse probability weighted (IPW)‐adjusted linear regression analysis to estimate adjusted mean (95% confidence interval) differences in estimated glomerular filtration rate (eGFR; ml/min/1.73 m 2 ) by mutation status, variant allele frequency (VAF%), blood cell counts, and neutrophil‐to‐lymphocyte ratio (NLR). We performed 11‐year longitudinal follow‐up of eGFR in all individuals. Compared to CHIP‐negative individuals, the mean differences in eGFR were −5.6 (−10.3, −0.8, p = .02) for CALR, −11.9 (−21.4, −2.4, p = 0.01) for CALR type 2, and −10.1 (−18.1, −2.2, p = .01) for CALR with VAF ≥ 1%. The IPW‐adjusted linear regression analyses showed similar results. NLR was negatively associated with eGFR. Individuals with CALR type 2 had a worse 11‐year longitudinal follow‐up on eGFR compared to CHIP‐negative individuals ( p = .004). In conclusion, individuals with CALR mutations, especially CALR type 2, had impaired kidney function compared to CHIP‐negative individuals as measured by a lower eGFR at baseline and during 11‐year follow‐up.